THE DEVELOPMENT OF E-LKPD BASED ON HIGH-ORDER THINKING SKILLS (HOTS) WITH 4D MODEL - Hartono, Jessica Kristanti; Juliani, Rita (UNIVERSITAS NEGERI MEDAN, 2022)
This research aims to know the level of validation and level of practicality of the development of e-LKPD based on HOTS with a 4D model of Doppler effect material from a material expert, media expert, teacher, and student. The research type is a 4D model but this research is limited to 3D steps that are defined, designed, and develop. The research population was students in SMA Negeri 3 Pematangsiantar Class XI Science. The sample research is taken by cluster sampling. In this research, the validators have an instrument with a questionnaire of development e-LKPD to know the level of validation. The instrument of this study was a questionnaire from a material expert, media expert, and teacher. The analysis results that development gets level validation and practicality are very worthy with 92,5% from the material expert, very worthy with 97,5% from the media expert, and very worthy with 95,2% from a teacher. Based on the data, the conclusion is that the development of e-LKPD based on HOTS with a 4D model on the Doppler effect is very worthy of validation and practicality.